Kebijakan dan Pengambilan Keputusan Pimpinan dalam Suatu Organisasi atau Pengorganisasian - Devi Syukri Azhari; Zihnil Afif; Ahmad Sabri; Hidayati Hidayati (Journal on Education, 2022)
The leadership role is a set of expected behavior, carried out by people in accordance with its position as a leader. The role of the leader is very large in making decisions and taking responsibility for the outcome. The decision reflects the character of a leader. Decision-making is central to the organization's activities are also a key leadership or the core of leadership. Leaders must be able to take decisions in a variety of situations, by choosing the best among a number of alternative alternatis decisions it faces. Alternatidf should be chosen that its smallest negative risk so as not to harm the organization. Leaders must be able to explain the reason – the reason for choosing one alternative decisions in a way that is most easily understood in order to get support in implementation.